USM AND UNIVERSITY OF BATH MOVING AHEAD WITH SMART PARTNERSHIP - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 23 February 2016 – Universiti Sains Malaysia (USM) is currently in discussions with the University of Bath (UoB), United Kingdom to realise the idea of implementing a collaboration to develop a number of academic programmes together.